World trade indicators 2008 : - Islam, Roumeen (The World Bank, 2008)
The World Bank’s World Trade Indicators (WTI) book plus CD-ROM provides more than 300 performance indicators measuring at-the-border and behind-the-border country trade policy, institutions, and outcomes from 1995 to 2007. The database allows each country to be ranked along any policy or performance dimension relative to others. Trade-at-a-Glance tables for the 210 countries in the database facilitate comparisons between countries in key areas. Complementing the rich database are Trade Briefs for 142 developing countries summarizing insights from the data and the main findings of analytical work conducted by the Word Bank, the IMF, and the WTO for individual countries. The World Trade Indicators 2008 companion volume highlights the main patterns in policy and performance revealed by the database grouping countries by region or income. The 20 best and 20 worst country rankings for a number of indicators are shown. For country policy makers, trade negotiators and their advisors, this volume provides the rich context within which to interpret a single country s standing on various dimensions. Business executives will gain new insights about the countries in which they and their competitors operate. And trade researchers will find tantalizing country stories on trade policy and institutional dimensions and trade outcomes. Country performance is benchmarked around five main pillars: 1. Border protection, such as tariffs and non-tariff barriers on imports of goods and services; 2. Market access barriers in the rest of the world to exports of goods; 3. Overall business and institutional environment; 4. Trade facilitation; 5. Trade outcomes, such as trade growth, integration, and diversification.